Complete denture fracture - A proposed classification system and its incidence in National Capital Region population: A survey - Shweta Choudhary (Wolters Kluwer Medknow Publications, 2019)
Aim: The complete denture fracture of denture may ruin the routine life of an edentulous patient. The aim of the present study was to propose and evaluate a new classification system for denture fractures. Settings and Design: Cross sectional -Survey. Materials and Methods: Ten dental laboratories in Delhi and the National Capital Region participated in the study for 2 years. The accurate assessment of fractured dentures received in the laboratories for repairs was done. A questionnaire with complete information along with photographs was used to classify the denture fracture. Statistical Analysis Used: Percentage (proportion) statistical test. Results: Out of 620 dentures, 164 (94 maxillary and 70 mandibular) were found with previous repair, soft liners, metal frame, or wire reinforcements which were excluded from the study. In the present study, 456 dentures were considered (256 maxillary and 200 mandibular). Class I fracture (midline) was the most common in both maxillary and mandibular dentures (46.87% in maxillary and 61% in mandibular) with high significance (P < 0.001). Class II and Class V were the second most common pattern of fracture in mandibular and maxillary dentures, respectively. There was no single case of Class III fracture for the mandibular dentures, and Class IV was the least common among the maxillary dentures. Conclusions: This study encourages further clinical studies for validation and reliability evaluation of proposed new classification system.